Inward Foreign Direct Investment and Welfare Nexus: The Impact of Foreign Direct Investment on Welfare in Developing Countries - Hossain, Md. Shakib; Kamal, Md. Shahin; Halim, Md. Rubaeth; Zayed, Nurul Mohammad (International Journal of Economics and Financial Issues, 2019)
It is an attempt to estimate the consequence on welfare because of foreign direct investment (FDI) in different developing countries, mainly incorporated with the panel data having 79 countries producing over 1,343 observations from 1998 to 2014. Panel unit root test, panel cointegration, vector error correction model, panel dynamic least squares, fully modified least square method, fixed effect model and random effect model have used for determining the consequence on welfare due to FDI. According to the vector error correction model, it interprets that there is a long run causality of the variables such as FDI, agglomeration, debt, governance, inflation, infrastructure, openness, bureaucracy and country risk with the welfare. Concentrating on panel dynamic least squares and fully modified least square method that interprets if the FDI goes up by 1 unit the welfare goes up 0.286751 and 0.227956 respectively and from the both fixed effect model and random effect model elucidate that FDI is a significant variable to explain the welfare. Keywords: Panel unit root test, panel cointegration, vector error correction model, foreign direct investment JEL Classifications: C23, F21, I3 DOI: https://doi.org/10.32479/ijefi.8465